2010
DOI: 10.1016/j.biomaterials.2010.01.104
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic hydrogels with pro-angiogenic properties

Abstract: To achieve the task of fabricating functional tissues, scaffold materials that can be sufficiently vascularized to mimic functionality and complexity of native tissues are yet to be developed. Here, we report development of synthetic, biomimetic hydrogels that allow the rapid formation of a stable and mature vascular network both in vitro and in vivo. Hydrogels were fabricated with integrin binding sites and protease-sensitive substrates to mimic the natural provisional extracellular matrices, and endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
336
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(353 citation statements)
references
References 31 publications
13
336
3
1
Order By: Relevance
“…However, the inherent chemical and physical properties of these natural materials have limited their clinical usage [14,15]. Recent studies have explored synthetic materials as a xeno-free and more clinically relevant alternative for both therapeutic angiogenesis [16,17] and vascularization of tissue-engineered constructs [18,19]. We recently reported that hyaluronic acid (HA) hydrogels can be engineered to precisely control the generation of functional human vascular networks by ECFCs [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the inherent chemical and physical properties of these natural materials have limited their clinical usage [14,15]. Recent studies have explored synthetic materials as a xeno-free and more clinically relevant alternative for both therapeutic angiogenesis [16,17] and vascularization of tissue-engineered constructs [18,19]. We recently reported that hyaluronic acid (HA) hydrogels can be engineered to precisely control the generation of functional human vascular networks by ECFCs [20].…”
Section: Introductionmentioning
confidence: 99%
“…165 Hydrogels were fabricated with integrin binding sites and protease-sensitive substrates to mimic the natural provisional ECM, and ECs cultured in these hydrogels organized into stable, intricate networks of capillary-like structures. The resulting structures were further stabilized by recruitment of mesenchymal progenitor cells that differentiated to a SMC lineage and deposited collagen IV and laminin.…”
Section: 폴리머 제38권 제2호 2014년mentioning
confidence: 99%
“…In addition, hydrolytic degradation is not representative of the cellularly mediated and dynamic process of proteolysis that takes place within the native ECM. Therefore, numerous studies have covalently incorporated peptide sequences susceptible to cleavage by cell-secreted proteases (i.e., plasmin-sensitive or MMPsensitive sequences) into PEG hydrogels thus manipulating gel degradation dynamically in response to cellularly mediated events (Gobin & West, 2002;Lee et al, 2007;Lutolf et al, 2003;Moon et al, 2007;Moon et al, 2010;Patterson & Hubbell 2010;Phelps et al, 2009;Seliktar et al, 2004;West & Hubbell, 1999;Zisch et al, 2003).…”
Section: Engineering Ecm Cues Into Peg Hydrogel Scaffoldsmentioning
confidence: 99%
“…Studies using UV-based freeradical photopolymerization for the formation of MMP-sensitive, VEGF-bearing PEGDA hydrogels as potential matrices for the induction of vascularization indicated that endothelial cell tubule formation and maintenance was directly affected by gel mechanical properties. Hydrogels formed with an intermediate polymer weight percentage of 10% resulted in the formation of tubules, while less crosslinked PEGDA matrices (7.5% PEG content) caused complete tubule regression, and matrices (15% PEG content) reduced tubule formation in vitro (Moon et al, 2010). PEG hydrogels of this intermediate stiffness were implanted into mouse cornea using a micropocket angiogenesis assay and resulted in neovascularization in the presence of vascular endothelial growth factor (VEGF) (Rogers et al, 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%